Wage Flexibility under Sectoral Bargaining - David Card; Ana Rute Cardoso (Institute of Labor Economics (IZA), 2021)
Sectoral contracts in many European countries set wage floors for different occupation groups. In addition, employers often pay a wage premium (or wage cushion) to individual workers. We use administrative data from Portugal, linked to collective bargaining agreements, to study the interactions between wage floors and wage cushions and quantify the impact of sectoral wage floors. Although wages exhibit a "spike" at the wage floor, a typical worker receives a 20% premium over the floor, with larger cushions for older and better-educated workers and at higher-productivity firms. Cushions also allow wages to covary with firm-specific productivity, even within sectoral agreements. Contract negotiations tend to raise all wage floors proportionally, with increases that reflect average productivity growth among covered firms. As floors rise, however, cushions are compressed, leading to an average passthrough rate of only about 50%. We find no evidence of employment responses to floor increases. Finally, we use a series of counterfactual simulations to show that real wage reductions during the recent financial crisis arose through reductions in real wage floors, reductions in real cushions, and a re-allocation of workers to lower wage floors. Offsetting these effects was a rapid rise in education of new cohorts, which in the absence of other factors would have led to rising real wages.
Keywords: J31; J41; J51; 330; sectoral bargaining; trade unions; wage flexibility